10.1016/s1558-0164(07)70254-7 (CrossRef Listing of Deleted DOIs, 2000)
Introduction Chronic rhinosinusitis (CRS) has been consistently associated with reduced quality of life, including limitations in mobility and daily activities. Wearable technology has demonstrated utility in tracking physical activity after surgical interventions, with limited studies on activity levels after sinus surgery. Methods We performed a retrospective review of Apple Health data from participants diagnosed with CRS who underwent sinus surgery at two tertiary academic centers. Daily activity metrics were aggregated over 12 months preoperatively and 2-13 months postoperatively following a 1-month washout period. Metrics analyzed included average daily steps, and other ambulatory activity elements. Pre- and post-surgical values were compared using Wilcoxon signed-rank tests. Results Among 51 CRS patients (mean age 37.7 ± 11.2 years), average daily step count significantly increased following surgery, from 7501.4 ± 4119.9 to 8843.5 ± 5107.3 per day (p = 0.003). Daily active energy burned rose from 335.5 ± 210.7 to 383.4 ± 244.8 kilocalories (p = 0.025), and daily distance walking or running increased (3.25 ± 1.88 to 3.80 ± 2.29 miles, p = 0.006). Daily exercise minutes and flights climbed also improved (p = 0.014 and p = 0.022, respectively). SNOT-22 scores demonstrated significant postoperative reductions, decreasing from 43.46 ± 24.18 to 21.15 ± 18.83, p < 0.001. Conclusion We observed CRS patients post-sinus surgery to have significant increases in activity metrics as measured by wearable technology. This pilot study suggests that postoperative recovery may extend beyond symptom relief to measurable changes in daily physical activity.